Comparative Study on the Role of Character Education in Shaping Social Studies Curricula in Japan and Indonesia - Dewicca Fatma Nadilla; Ersis Warmansyah Abbas; Mutiani Mutiani (Yupa: Historical Studies Journal, 2025)
This study explores the character values as the foundation for Social Studies curriculum development through a comparative analysis between Indonesia and Japan. Employing a qualitative descriptive method with content analysis of official curriculum documents, the research reveals that both nations place strong emphasis on character formation, though shaped by distinct historical, cultural, and philosophical contexts. Japan’s approach is deeply rooted in a consistent and centralized education system that blends constitutional nationalism, cultural collectivism, and Bushidō ethics into daily school life. Meanwhile, Indonesia has experienced a dynamic transformation from ideological and centralized models to more flexible, contextual, and culturally responsive curricula, particularly under the Merdeka Curriculum. The findings underscore the need for localized pedagogical strategies and enhanced teacher competencies to effectively translate character education into practice, enabling the development of socially responsible, globally aware citizens grounded in national values.